2008
DOI: 10.1111/j.1467-9280.2008.02064.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Memory

Abstract: We recently proposed that human memory systems are "tuned" to remember information that is processed for survival, perhaps as a result of fitness advantages accrued in the ancestral past. This proposal was supported by experiments in which participants showed superior memory when words were rated for survival relevance, at least relative to when words received other forms of deep processing. The current experiments tested the mettle of survival memory by pitting survival processing against conditions that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
116
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(132 citation statements)
references
References 15 publications
10
116
4
Order By: Relevance
“…As anticipated, the pleasantness condition led to the lowest recall performance compared to the other three encoding conditions. In line with previous findings (Nairne & Pandeirada, 2008a, 2008b, 2010aNairne et al, 2007Nairne et al, , 2008Nairne et al, , 2009), we found that survival processing led to better recall than pleasantness processing. Recall performance was lower under the survival condition than under the World-War-III and life-after-death conditions.…”
Section: Discussion Of Studysupporting
confidence: 93%
See 3 more Smart Citations
“…As anticipated, the pleasantness condition led to the lowest recall performance compared to the other three encoding conditions. In line with previous findings (Nairne & Pandeirada, 2008a, 2008b, 2010aNairne et al, 2007Nairne et al, , 2008Nairne et al, , 2009), we found that survival processing led to better recall than pleasantness processing. Recall performance was lower under the survival condition than under the World-War-III and life-after-death conditions.…”
Section: Discussion Of Studysupporting
confidence: 93%
“…Thus, the advantage of survival processing in long-term encoding over all other deep encoding conditions is not always found. Here, in Study 1, we replicated the recall advantage of survival processing over the deep encoding pleasantness condition found in previous studies (Nairne & Pandeirada, 2008a, 2008b, 2010aNairne et al, 2007Nairne et al, , 2008Nairne et al, , 2009). However, it has been observed that this enhanced retention due to encoding words in a survival scenario is not always found when compared with control conditions previously found to be generally less optimal, for example self-reference (see Klein, 2012).…”
Section: Limitations Of the Survival Effectsupporting
confidence: 88%
See 2 more Smart Citations
“…Prioritization can enhance memory in the form of emotional salience (Hamann, 2001), evolutionary significance (Nairne et al ., 2008), or reward (Castel et al ., 2007), as in the present study. Here, we show that beneficial effects of reward on memory, as indicated by better memory for HL versus nHL content, are present a few minutes, 1 week, and even 6 weeks after encoding.…”
Section: Discussionmentioning
confidence: 99%